Sotos syndrome with hypodontia - A. P. CALLANAN, P. ANAND & E. C. SHEEHY (Paediatric Dentistry, 2006)
Sotos syndrome was first reported by Sotos et al. in 1964 [1]. The main clinical features of the syndrome are tall stature, gigantism, a prominent forehead (dolichocephaly), advanced bone age and learning disability [2].